Economic analysis of an energetically self-supporting farm – possibilities of biogas production in particular - Vida, Adrienn; Dunay, Anna (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
The use of renewable energy sources has been an important topic of scientific researches and many studies since the first energy crisis (1973) in different aspects through either specific or complex examinations. Until the beginning of the 21st century, national and international objectives were focused on the use of different types of renewable energy sources (i.e. solar, wind, geothermal and biomass energy) without any limits, but nowadays the utilization of sustainable potential in a complex way – considering economic, ecologic and social aspects – has been come to the front. The scale of units has also become sophisticated: the small scale units which is based on local energy sources are more and more important elements of changeable energy structure. The topic of present publication is the analysis of a complex farm activity and in the center of the paper is the research of the concept of energetically selfsupport agriculture in the economical aspect.
Keywords: renewable energy sources; waste agricultural biomass; biogas